Ginsenoside Re ameliorates thioacetamide-induced acute liver injury through inhibiting autophagy-NLRP3 inflammasome pathway - Lin, Jing; Wang, Huan; Zhao, Ruowei; Li, Shaohua; Chang, Dennis; Zheng, Yanfang; Zhou, Xian; Huang, Rui; Huang, Mingqing (Frontiers in Pharmacology, 2025)
BackgroundGinsenoside Re (G-Re), a unique ginsenoside almost exclusively found in Araliaceae plants, is a promising therapeutic agent for attenuating liver injury. This study aims to investigate the liver-protective effects of G-Re and the underlying mechanisms in acute liver injury models.MethodsMale C57BL/6 mice were intraperitoneally injected with various agents induce the acute liver injury model after pre-treatment with G-Re (5–20 mg/kg, oral gavage). Additionally, the phosphoinositide 3-kinases (PI3K) inhibitor LY294002 and the mammalian target of rapamycin (mTOR) inhibitor RAPA were co-administered with G-Re in the thioacetamide (TAA)-induced rat hepatic stellate cell line (HSC-T6) to explore the mechanisms associated with G-Re.ResultsG-Re at (20 mg/kg) protected liver against thioacetamide (TAA), ethanol, acetaminophen, and D-Galactosamine-induced liver injury in C57BL/6 mice. G-Re reduced serum levels of aspartate aminotransferase (AST) from 151.98 to 40.24 U/L and alanine aminotransferase (ALT) from 392.04 to 49.43 U/L. Both in vivo and in vitro studies consistently showed that G-Re decreased mRNA expression levels of key pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α) and interleukin-1β (IL-1β). Additionally, G-Re dose-dependently downregulated the protein expression of cyclooxygenase-2 (COX-2), inducible nitric oxide synthase (iNOS), NOD-like receptor protein 3 (NLRP3), cysteinyl aspartate specific proteinase −1 (caspase-1), interleukin-18 (IL-18), and IL-1β. In addition, our results suggested that the suppression of autophagy by G-Re may play a crucial role in its ability to inhibit the NLRP3 inflammasome. Notably, this regulatory effect on autophagy appears to be mediated through the phosphatidylinositide 3-kinases/protein kinase B/mammalian target of rapamycin (PI3K/AKT/mTOR signaling pathway). G-Re inhibits autophagy in both cellular and animal models by downregulating the expression of light chain 3-II (LC3-II), Beclin-1, and sequestosome-1 (p62) through this pathway. Furthermore, the PI3K inhibitor LY294002 and the mTOR inhibitor rapamycin (RAPA) were shown to partially reverse the inhibitory effects of G-Re on autophagy and inflammation in HSC-T6 cells. These results further support the notion that reactivation of autophagy can counteract G-Re–mediated suppression of NLRP3 and caspase-1 expression.ConclusionThis study highlights G-Re as a promising therapeutic candidate for liver injury, acting through inhibition of autophagy and inflammation via the PI3K/AKT/mTOR signaling pathway.